Compact MIMO antenna design for upcoming 5G applications - K. , Srinivasa Naik; Roy, Sourav; D., Madhusudan; S., Aruna (International Journal of Psychosocial Rehabilitation, 2020)
In this article, we designed a low-cost MIMO antenna for 5G-based IoT applications. The antenna covers the frequency spectra from 25.8 to 29.4 GHz. The gain found was near about 5.7 dBi at 28 GHz. The antenna is designed, simulated, and analyzed on ANSYS HFSS. The ECC and DG performance of the four-element MIMO antenna is studied, and it is found that both performances are useful in that range. The different antenna structures analyzed in MIMO antenna. The maximum antenna dimension found near about 9.48×7.36 mm2.